The economic legacy of Marcos - Gerardo P. Sicat (University of the Philippines, School of Economics (UPSE), 2011)
Ferdinand E. Marcos was the Philippine president from 1966 to 1986, a period exceeding twenty years. After serving as a two-term president of the Philippines from 1966-1972, he declared martial law under the constitution to assume dictatorial powers to tame the political chaos that was then engulfing the nation. In 1981, he ended the martial law period. The political framework that he adopted was patterned after the 1973 Constitution with amendments introduced and accepted by popular referendum concerning an elected parliament. He was driven from power in 1986. This paper reviews the economic and social contributions that his years in office brought to the country. During his period of rule, there were major reforms in government organization, in the provision of public infrastructure, and in social and economic development. In making the final accounting for Marcos, the paper concludes that the balance sheet is very positive. Many of the problems that continue to hound the nation today are the result of decisions taken during the transition from Marcos by the successor government. These mistakes are discussed. This paper contributes to the proper assessment of the country's long term economic and social problems. Naturally, the judgment of history will be made through the future assessments of social historians, economists, and other social scientists. This paper represents one such analysis.
Keywords: 330; Philippine economic history; economic development; Ferdinand Marcos; political economy; economic policy; Wirtschaftswachstum; Wirtschaftspolitik; Infrastrukturpolitik; Wirtschaftsgeschichte; Philippinen